Brewers’ Spent Grain from Different Types of Malt: A Comprehensive Evaluation of Appearance, Structure, Chemical Composition, Antimicrobial Activity, and Volatile Emissions - Aleksander Hejna; Joanna Aniśko-Michalak; Katarzyna Skórczewska; Mateusz Barczewski; Paweł Sulima; Jerzy Andrzej Przyborowski; Hubert Cieśliński; Mariusz Marć (Molecules, 2025)
Beer is the third most popular beverage in the world, and its production is distributed uniformly between the biggest continents. Considering the environmental aspects, the utilization of brewing by-products, mainly brewers’ spent grain (BSG), is essential on a global scale. The beer revolution, lasting over a few decades, significantly diversified the beer market in terms of styles, and therefore, also its by-products, which should be characterized appropriately prior to further application. Herein, the presented study investigated the unprecedented number of 22 different variants of brewers’ spent grain, yielded from the production of various beer styles, enabling their proper comparison. A comprehensive by-product characterization revealed an almost linear relationship (Pearson correlation coefficients exceeding 0.9) between the color parameters (L*, a*, browning index) of beer and generated spent grain, enabling a prediction of BSG appearance based on beer color. Applying wheat or rye malts increased the content of extractives by over 40%, reducing cellulose content by as much as 45%. Thermal treatments of malts (kilning or smoking) also reduced extractive content and limited antioxidant activity, often by over 30%. A lack of husk for wheat or rye reduced the crystallinity index of spent grain by 21–41%, while the roasting of barley efficiently decomposed the less stable compounds and maintained the cellulose crystalline structure. All the analyzed BSG samples were characterized by low volatile emissions and very limited antimicrobial activity. Therefore, their harmfulness to human health and the environment is limited, broadening their potential application range.